Time Perspectives and Career Anxiety Among Vietnamese teacher education undergraduates - Pham Ngoc Thien Nguyen; Khanh-Trinh Tran (Je-LKS: Journal of E-Learning and Knowledge Society)
This study examined the relationship between time perspectives—present fatalistic, present hedonistic, and future—and career anxiety among 354 Vietnamese teacher education undergraduates (68.4% female). The findings show that present fatalistic and present hedonistic time perspectives are positively correlated with career anxiety and its dimensions, while a future time perspective (FTP) is negatively correlated with career anxiety. The study also highlights that lower socioeconomic status (SES) is linked to higher present fatalistic, lower present hedonistic, and variations in career ambiguity. The results suggest that promoting a future-oriented mindset may help reduce career anxiety. Additionally, the study emphasizes the significant role of employment pressure as a key source of career-related stress, underscoring the importance of integrating stress management and coping strategies into career development programs. Furthermore, notable differences in time perspectives and career ambiguity across SES groups highlight the need for targeted interventions. The study concludes with a discussion of its implications and limitations.